Heterorhabditis bacteriophora symbiotic and axenic nematodes modify the Drosophila melanogaster larval microbiome - Mallick, Sreeradha; Pavloudi, Christina; Saw, Jimmy; Eleftherianos, Ioannis (Frontiers in Microbiology, 2025)
The Drosophila melanogaster microbiome is crucial for regulating physiological processes, including immune system development and function. D. melanogaster offers distinct advantages over vertebrate models, allowing a detailed investigation of host-microbiota interactions and their effects on modulating host defense systems. It is an outstanding model for studying innate immune responses against parasites. Entomopathogenic nematodes (EPNs) activate immune signaling in the fly, leading to immune responses to combat infection. However, the impact of EPN infection on the host larval microbiome remains poorly understood. Therefore, we investigated whether EPN infection affects the D. melanogaster larval microbiome. We infected third-instar D. melanogaster larvae with Heterorhabditis bacteriophora symbiotic nematodes (containing Photorhabdus luminescens bacteria) and axenic nematodes (devoid of symbiotic bacteria). Drosophila melanogaster microbiome analysis revealed statistically significant differences in microbiome composition between uninfected and EPN-infected larvae. Notably, infection with axenic nematodes resulted in 68 unique species, causing a significant shift in the D. melanogaster larval microbiome and an increase in bacterial diversity compared to larvae infected with symbiotic nematodes. This suggests that the absence of the endosymbiont creates ecological niches for unique species and a more diverse microbiome in larvae infected with the axenic nematodes. This research will enhance our understanding of microbial species within the D. melanogaster microbiome that regulate homeostasis during nematode infection. These insights could be beneficial in developing innovative strategies for managing agricultural pests and disease vectors.